Catatonia. (3rd June 2016) - Walther, Sebastian; Strik, Werner
Abstract : One of the most exciting psychiatric conditions is the bizarre psychomotor syndrome called catatonia, which may present with a large number of different motor signs and even vegetative instability. Catatonia is potentially life threatening. The use of benzodiazepines and electroconvulsive therapy (ECT) has been efficient in the majority of patients. The rich clinical literature of the past has attempted to capture the nature of catatonia. But the lack of diagnostic clarity and operationalization has hampered research on catatonia for a long time. Within the last decades, it became clear that catatonia had to be separated from schizophrenia, which was finally accomplished in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). In DSM-5, catatonia syndrome may be diagnosed as a specifier to major mood disorders, psychotic disorders, general medical conditions, and as catatonia not otherwise specified. This allows diagnosing the syndrome in a large variety of psychiatric disorders. Currently, the pathobiology remains widely unknown. Suspected neurotransmitter systems include gamma-aminobutyric acid (GABA) and glutamate. Neuroimaging reports pointed to reduced resting state activity and reduced task activation in motor areas of the frontal and parietal cortex. The new classification of catatonia will foster more clinical research and neuroscientific approaches by testing catatonia in various populations and applying stringent criteria. The scarce number of prospective trials will hopefully increase, as more trials will be encouraged within a more precise concept of catatonia.